Capital Structure and Risk Management in Enhancing Financial Performance: The Moderating Role of CSR in Indonesian Banking Sector - Aliyah Fadhilah; Luky Afriliyana; Mardiyani; Nurhana Dhea (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
The banking sector constitutes a foundational pillar in maintaining economic stability, yet its financial performance continues to face persistent challenges arising from internal capital management and exposure to credit risk. This study seeks to evaluate the extent to which financial soundness, reflected through capital strength and loan quality, influences profitability, and whether socially oriented initiatives condition these relationships. Employing a quantitative approach, the analysis draws upon firm-level data from Indonesian commercial banks over a four-year period, utilizing regression-based techniques to examine both direct effects and interactive influences. The results indicate that capital strength does not exert a statistically significant impact on profitability, and socially oriented programs do not moderate this relationship. Conversely, such programs are found to intensify the adverse effect of poor loan quality on financial performance, suggesting that, in the absence of strategic alignment, social initiatives may exacerbate financial pressures. This study contributes a novel perspective by reconceptualizing socially driven programs as conditional financial variables rather than solely reputational tools. The findings imply that policy and managerial decisions must integrate social objectives with prudent risk oversight to enhance sustainable banking performance.